2014
DOI: 10.4049/jimmunol.1302608
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Enhances Macrophage TLR Expression and MyD88-Mediated Signal Transduction To Potentiate Inducible Inflammatory Responses

Abstract: Circulating monocytes carrying human cytomegalovirus (HCMV) migrate into tissues, where they differentiate into HCMV-infected resident macrophages that upon interaction with bacterial products may potentiate tissue inflammation. Here we investigated the mechanism by which HCMV promotes macrophage-orchestrated inflammation using a clinical isolate of HCMV (TR) and macrophages derived from primary human monocytes. HCMV infection of the macrophages, which was associated with viral DNA replication, significantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 73 publications
(66 reference statements)
4
51
0
Order By: Relevance
“…In the absence of HIV-1, induction of replicating CMV has been shown to occur with the terminal differentiation of monocytes to myeloid dendritic cells, 49 and in vitro studies have demonstrated that monocyte to macrophage differentiation leads to production of infectious virus. [50][51][52] If HIV-1 infection activates monocytes and macrophages, 53 it is likely that CMV could be reactivated and replicate leading to an inflammatory response. In our study the association of CMV IgG with sCD14 within the HIV-1 viremic group, which was not present in the HIV-uninfected group, suggests that coinfection and long-term interaction of HIV-1 and CMV may lead to the development of serious non-AIDS events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of HIV-1, induction of replicating CMV has been shown to occur with the terminal differentiation of monocytes to myeloid dendritic cells, 49 and in vitro studies have demonstrated that monocyte to macrophage differentiation leads to production of infectious virus. [50][51][52] If HIV-1 infection activates monocytes and macrophages, 53 it is likely that CMV could be reactivated and replicate leading to an inflammatory response. In our study the association of CMV IgG with sCD14 within the HIV-1 viremic group, which was not present in the HIV-uninfected group, suggests that coinfection and long-term interaction of HIV-1 and CMV may lead to the development of serious non-AIDS events.…”
Section: Discussionmentioning
confidence: 99%
“…50 Reactivation of CMV may result in production of biomarkers of inflammation and immune activation such as sCD14, IL-6, sCD163, and IP10. 22,47,51,57 An increase in CMV IgG and CMV-specific T cells may result in temporary control of infection, but the potential for additional cycles of reactivation and inflammation would be predicted to result in cellular and tissue damage. The extent of the damage would depend on the body compartment(s) involved and the magnitude and frequency of the immunological response to the infections.…”
Section: /Cd8mentioning
confidence: 99%
“…When expression of chemokines is compared between infected and transfected HUVEC, quite a few more chemokines could be detected in infected cells, supporting previous studies of upregulation of growth factors/chemokine/cytokines following HCMV infection (Frascaroli et al, 2006;Hamilton et al, 2012;Li et al, 2014;Murayama et al, 1997;Scott et al, 2012;Smith et al, 2014;Weseslindtner et al, 2014). Indeed, we found 18 chemokines elevated in HCMV-infected HUVEC.…”
Section: Discussionsupporting
confidence: 76%
“…Infection with CMV enhances monocyte transendothelial migration and motility (Smith et al, 2004a(Smith et al, , 2007, as well as monocyte differentiation into macrophages (Smith et al, 2004a,b;Chan et al, 2012), thereby promoting the dissemination of CMV-infected mononuclear phagocytes to the tissues. In addition, CMV infection upregulates macrophage expression of surface CD14 and TLRs 2, 4, and 5 and enhances the capacity of monocyte-derived macrophages to produce inflammatory cytokines in response to the cognate TLR ligands L. monocytogenes, Escherichia coli lipopolysaccharide, and Salmonella typhimurium flagellin ( Smith et al, 2014). Infection of macrophages with CMV induces adaptor protein MyD88 expression and enhances inducible phosphorylation of IκBα and NF-κB, promoting the translocation of NF-κB p65 into the nucleus for activation of inflammatory cytokine genes and the production of proinflammatory cytokines (Smith et al, 2014).…”
Section: Intestinal Macrophages In Mucosal Infectionsmentioning
confidence: 99%
“…In addition, CMV infection upregulates macrophage expression of surface CD14 and TLRs 2, 4, and 5 and enhances the capacity of monocyte-derived macrophages to produce inflammatory cytokines in response to the cognate TLR ligands L. monocytogenes, Escherichia coli lipopolysaccharide, and Salmonella typhimurium flagellin ( Smith et al, 2014). Infection of macrophages with CMV induces adaptor protein MyD88 expression and enhances inducible phosphorylation of IκBα and NF-κB, promoting the translocation of NF-κB p65 into the nucleus for activation of inflammatory cytokine genes and the production of proinflammatory cytokines (Smith et al, 2014). These findings indicate a mechanism by which CMV potentiates bacteriainduced proinflammatory cytokines and chemokines by monocyte-derived macrophages (Smith et al, 1992;Peterson et al, 1992;Yurochko and Huang, 1999;Redman et al, 2002;Kossmann et al, 2003;Maheshwari et al, 2006).…”
Section: Intestinal Macrophages In Mucosal Infectionsmentioning
confidence: 99%